The periodic solution for some systems of nonlinear integro-differential equations of Volterra type. - Raad Putrus; Ghada Jameel (College of Education for Pure Sciences, 2008)
ABSTRACT In this paper we investigate the existence and approximation of the periodic solution for a system of nonlinear integro-differential equations of Volterra type. The numerical-analytic method has been used to study the periodic solutions of the non-linear ordinary differential equations that were introduced by A.M. Samoilenko.